Lightning related fatalities in livestock: Veterinary expertise and the added value of lightning location data. Issue 1 (January 2015) - Vanneste, E.; Weyens, P.; Poelman, D.R.; Chiers, K.; Deprez, P.; Pardon, B.
Highlights A retrospective analysis of 410 declarations of lightning related fatalities (LRF) in livestock is presented. 52.9% of the declarations were not compatible with fatal lightning stroke. Pathognomonic singe lesions were present in only 43.3% of the confirmed cases. Combining the veterinary expert investigation with lightning detection data resulted in the most correct LRF diagnosis.